PENGARUH LITERASI KEUANGAN DAN FINANCIAL TECHNOLOGY TERHADAP INKLUSI KEUANGAN PADA PELAKU UMKM SEKTOR OLAHAN MAKANAN DAN MINUMAN DI KECAMATAN TAMPAN KOTA PEKANBARU - Oeli, Duta Wira Abhyasa; ', Ruzikna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to determine the effect of financial inclusion on the sustainability of MSME, determine the effect of financial management on the sustainability of MSME, and find out whether financial inclusion and financial management have an effect on the sustainability of MSME. The research method used is a quantitative method and uses secondary and primary data. Primary data was obtained from respondents who were collected through a questionnaire consisting of 24 questions. The sample consisted of 95 MSME business actors in the processed food and beverage sector from a population of 1856 business actors using a purposive random sampling technique. The measurement scale uses a Likert scale. Data analysis includes: descriptive statistics, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, t test, f test, and coefficient of determination test. The data analysis technique for this research uses SPSS 25. The results of this research show, (1) There is a significant influence of financial inclusion on business sustainability among MSME actors in the food and beverage processing sector in Tampan District, (2) There is a significant influence of financial management on sustainability business among MSME actors in the food and beverage sector in Tampan District, and (3) There is a significant influence of financial inclusion and financial management on financial inclusion among MSME actors in the food and beverage sector in Tampan District. Keywords: financial inclusion, financial management and sustainability of MSME.